Epidemiology of vaccine-preventable diseases in Japan: considerations for pre-travel advice for the 2019 Rugby World Cup and 2020 Summer Olympic and Paralympic Games - Griffith, Matthew M.; Fukusumi, Munehisa; Kobayashi, Yusuke; Matsui, Yusuke; Nishiki, Shingo; Shimbashi, Reiko; Morino, Saeko; Sunagawa, Tomimasa; Taya, Keiko; Matsui, Tamano; Oishi, Kazunori (Western Pacific Surveillance and Response, 2018)
Introduction: In 2019 and 2020, Japan will host two international sporting events estimated to draw a combined 22 million visitors. Mass gatherings like these ones increase the risk of spread of infectious disease outbreaks and international transmission. Pre-travel advice reduces that risk.Methods: To assist ministries of health and related organizations in developing pre-travel advice, we summarized national surveillance data in Japan (2000–2016, to the extent available) for rubella, invasive pneumococcal disease, measles, non-A and non-E viral hepatitis, hepatitis A, invasive Haemophilus influenzae disease, tetanus, typhoid fever, invasive meningococcal disease, Japanese encephalitis, influenza, varicella, mumps and pertussis by calculating descriptive statistics of reported cases and reviewing trends. (See Annex A for details of reviewed diseases.)Results: Our findings showed notable incidences of rubella (1.78 per 100 000 person-years), influenza (243.5 cases per sentinel site), and mumps (40.1 per sentinel site); seasonal increases for influenza (November–May) and Japanese encephalitis (August–November); and a geographical concentration of Japanese encephalitis in western Japan. Measles cases decreased from 11 013 in 2008 to 35 in 2015, but outbreaks (n = 165 cases) associated with importation occurred in 2016. Though invasive meningococcal disease incidence was only 0.03 per 100 000, international transmission occurred at a mass gathering in Japan in 2015.Discussion: Ministries of health and related organizations should use these findings to develop targeted pre-travel advice for travellers to the 2019 Rugby World Cup and the 2020 Summer Olympic and Paralympic Games, especially for mumps, measles, rubella, influenza, and meningitis. Travellers with increased exposure risk should also be advised about hepatitis A and Japanese encephalitis.